2018
DOI: 10.1029/2017tc004926
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Analysis Along the Sunda Trench: Bending, Buckling and Plate Coupling

Abstract: The bathymetry and free-air gravity data offshore Sunda trench are used here to analyze the flexural forebulge and bending moment variations along the Southeast Asian subduction zone. The observed bathymetry is corrected for various effects such as the sediment loading, lithosphere age, and the gravity-derived isostatically compensated topography, which gave rise to the flexural deformation surface of the subducting Indo-Australian plate. From this, 28 across-trench sections were constructed to model the plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
2
6
0
Order By: Relevance
“…Raghuram et al. (2018) used forebulge flexure models to argue that high plate coupling occurs in Sumatra, where the slab is short, due to horizontal forcing resulting from the adjacent subduction of the longer Java slab ( P ‐wave anomalies in Figure 9a). This may be analogous to imposing a constant v c in our models with young age SP and episodic stalling.…”
Section: Discussion: Estimates Of Interface Stress and Comparison To mentioning
confidence: 99%
See 1 more Smart Citation
“…Raghuram et al. (2018) used forebulge flexure models to argue that high plate coupling occurs in Sumatra, where the slab is short, due to horizontal forcing resulting from the adjacent subduction of the longer Java slab ( P ‐wave anomalies in Figure 9a). This may be analogous to imposing a constant v c in our models with young age SP and episodic stalling.…”
Section: Discussion: Estimates Of Interface Stress and Comparison To mentioning
confidence: 99%
“…Heuret et al (2012) classified both Sumatra and Java as having similar overriding plate regimes, however they found that Java has relatively thinner trench sediment fill that may discourage the occurrence of great earthquakes. Raghuram et al (2018) used forebulge flexure models to argue that high plate coupling occurs in Sumatra, where the slab is short, due to horizontal forcing resulting from the adjacent subduction of the longer Java slab (P-wave anomalies in Figure 9a). This may be analogous to imposing a constant v c in our models with young age SP and episodic stalling.…”
Section: Along-strike Variation In Slab Dynamicsmentioning
confidence: 99%
“…More data is needed to learn better understanding of distributional localities of M. owstoni in Indonesian waters, and to determine probably some threats of its populations in the future. Northwest Sumatra and southwest off Java waters, two locations known of M. owstoni in Indonesian waters are part of Sunda Trench where depth variation is about 200-600 m (Raghuram et al 2018). This deepwater seas is an ideal and potential habitat of M. owstoni.…”
Section: G1 G2mentioning
confidence: 98%
“…The depth of the subduction in this area is a proxy for slab pull forces (Raghuram et al., 2018), and in a two‐dimensional force balance, the low slab pull cannot explain the coupling along this trench nor the oblique convergence. Several works addressed the seismic regime near Sumatra, for example, suggesting the role of the upper plate thickness and its tectonic regime (Grevemeyer and Tiwari, 2006), localized gravitational forearc collapse (Craig & Copley, 2018), and additional far‐field stresses (Raghuram et al., 2018). Global modeling has shown the control of the Java slab on the Sunda margin convergence velocities, which are faster along the Java segment and increasingly oblique northward (Ghosh & Holt, 2012; Stadler et al., 2010), while the relation to gradients in plate boundary velocities (Gordon & Houseman, 2015; Sandiford et al., 2005) have been invoked to explain the deformation and seismicity in the Sumatran segment.…”
Section: Introductionmentioning
confidence: 99%